Fundamentals of international financial management (PHI Learning pvt limited, 2016)
This concise and compact text explains, with great precision and clarity, the basic concepts theories and prctices of international business. The text is so significant because , in today's modern globalized economic environment, international transactions form an integral part of economic activities.